The Effect of Balinese Arak on Spermatozoa Motility in Wistar Rats (Rattus norvegicus) - Ni Putu Wulan Prasanti; I Gusti Ngurah Pramesemara; I Made Oka Negara; I Gusti Ayu Dewi Ratnayanti (Indonesian Andrology and Biomedical Journal, 2026)
Background : Infertility is a global health problem affecting 1 in 6 people worldwide, with one major cause being impaired spermatozoa motility, which is negatively affected by alcohol consumption. Balinese arak, a traditional alcoholic beverage in Bali with a high ethanol content, has the potential to reduce sperm quality. Objective : This study aimed to evaluate the effect of Balinese arak administration on spermatozoa motility in Wistar rats (Rattus norvegicus). Methods : This experimental study used a randomized post-test only control group design conducted at the Integrated Biomedical Laboratory Unit, Faculty of Medicine, Udayana University. A total of 13 male Wistar rats (Rattus norvegicus) were randomly allocated into a control group (P1, n=6) receiving distilled water and a treatment group (P2, n=7) receiving Balinese arak at a dose of 0.5mL/200 g body weight/day for 45 days. Sperm motility (total, progressive, non-progressive, and immotile) was examined using a light microscope (400x magnification) and analyzed using SPSS 26 with an independent t-test. Results : The mean total sperm motility in the treatment group (49.57±5.639%) was lower compared to the control group (69.00±4.865%). Independent t-test demonstrated significant differences in total motility (p=0.026), non-progressive motility (p=0.015), and immotile sperm (p=0.026). However, progressive motility did not differ significantly between the two groups (p=0.354). Conclusion : Administration of Balinese arak resulted in a significant decrease in total and non-progressive motility and a significant increase in immotile sperm in Wistar rats, but no significant effect on progressive motility was found. Keywords : Balinese Arak, Spermatozoa Motility, Wistar Rats